Survive the island - Avatar, Ari (New York, NY : Scholastic Inc., 2024)
Ari is super excited for the holidays! He finally gets the chance to relax. That is, until he finds out that his sister is joining him on vacation. So lame! The trip soon takes an unexpected turn that leaves Ari and his friends stranded on a deserted island. How will they survive? And what about that strange buzzing that's coming from the island core?
An unofficial Roblox book--Front cover.
3-6
Keywords: Roblox (Computing platform) -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Islands -- Juvenile fiction; Survival -- Juvenile fiction; Roblox (Computing platform) -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Islands -- Fiction; Survival -- Fiction; Adventure and adventurers -- Fiction; Action and adventure fiction; Fantasy fiction